A HT column GC/MS method for the determination of anthraquinone and its toxic impurities in paper products. Issue 15 (7th August 2015) - Yang, Ki-Ryeol; Seo, Hee Seung; Lee, Yong Sup; Choi, Man Ho; Hong, Jongki
<x xml:space="preserve">Abstract</x> A high-temperature (HT) column gas chromatography-mass spectrometry (GC/MS) method was developed and validated for the measurement of anthraquinone (AQ) and its toxic impurities in various paper food packaging products.